Computer security - ESORICS 2015 : 20th European Symposium on Research in Computer Security, Vienna, Austria, September 21-25, 2015, proceedings /: 20th European Symposium on Research in Computer Security, Vienna, Austria, September 21-25, 2015, proceedings. (2015) - Unknown
No abstract available